2007
DOI: 10.3748/wjg.v13.i13.1962
|View full text |Cite
|
Sign up to set email alerts
|

Lactobacillusplantarum inhibits epithelial barrier dysfunction and interleukin-8 secretion induced by tumor necrosis factor-α

Abstract: AIM:To determine whether Lactobacillus plantarum can modify the deleterious effects of tumor necrosis factor-a (TNF-a) on intestinal epithelial cells. METHODS:Caco-2 cells were incubated with TNF-a alone or in the presence of L. plantarum . Transepithelial electrical resistance was used to measure epithelial barrier function. Interleukin 8 (IL-8) secretion by intestinal epithelial cells was measured using an ELISA. Cellular lysate proteins were immunoblotted using the anti-extracellular regulated kinase (ERK),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
47
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(48 citation statements)
references
References 25 publications
1
47
0
Order By: Relevance
“…The results of this study provide a highly plausible explanation for the reported protective effects of L. plantarum and other probiotic strains on barrier disruption by inflammatory cytokines, chemicals, and infectious agents (13,18,20,28,32,34,35,48). However, increased mucin production, immunomodulation, pathogen inhibition, and effects on the resident microbiota could also be contributory factors, particularly in vivo.…”
Section: G855mentioning
confidence: 58%
See 1 more Smart Citation
“…The results of this study provide a highly plausible explanation for the reported protective effects of L. plantarum and other probiotic strains on barrier disruption by inflammatory cytokines, chemicals, and infectious agents (13,18,20,28,32,34,35,48). However, increased mucin production, immunomodulation, pathogen inhibition, and effects on the resident microbiota could also be contributory factors, particularly in vivo.…”
Section: G855mentioning
confidence: 58%
“…In vitro studies using polarized Caco-2 cell monolayers have also shown protective effects of L. plantarum strains on the reduction of TER induced by tumor necrosis factor-␣ (TNF-␣) and Listeria monocytogenes (L. monocytogenes) (17,18). In the latter study, changes in the total amount of cellular ZO-1 were implicated in the opposing effects of L. plantarum and L. monocytogenes, but effects on TJ composition itself were not studied.…”
Section: Translational Highlights This Study Demonstrates That In Thmentioning
confidence: 99%
“…Exposure to pro-inflammatory cytokines IFN-c or TNF-a, individually, and over long time periods (36-48 h), decreases barrier function in model polarized epithelial monolayers (Ko et al, 2007;Ma et al, 2004;Utech et al, 2005). However, the two cytokines also act synergistically to impair epithelial barrier function (Wang et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Evidence has indicated that endogenous carbon monoxide (CO), a biproduct of inducible heme oxygenase can modulates inflammation. Many experiments have demonstrated that the administration of exogenous CO inhibits the lipopolysaccharide-induced production of cytokines both in vivo and in vitro, and consequently exhibits important cytoprotective functions and anti-inflammatory properties that are beneficial for the resolution of acute inflammation [16][17][18][19] . Recently, transitional metal carbonyls have been identified as potential CO-releasing molecules (CORM) with the potential to facilitate the pharmaceutical use of CO by delivering it to tissues and organs [20] .…”
Section: Introductionmentioning
confidence: 99%